A clinical case of diagnosis of autoimmune hepatitis at the stage of liver cirrhosis - O. A. Svitlytska; O. V. Riabokon; A. O. Svitlytskyі; N. H. Horbatkova; E. V. Kotliarevska (Zaporozhye State Medical University, 2023)
The aim of the work is to analyze a clinical case of autoimmune hepatitis (АІН) diagnosis at the stage of cirrhosis in a 40-year-old female patient and to remind practicing doctors about the serious consequences of this disease. Materials and methods. A clinical case of AIH diagnosed according to the criteria of the International Autoimmune Hepatitis Group (2008) at the stage of cirrhosis in a 40-year-old female patient was analyzed. A puncture liver biopsy with a morphological study of the hepatobioptate was also performed to verify the diagnosis. Results. The analysis of the clinical case of AIH in a 40-year-old female patient revealed a delayed diagnosis of AIH at the cirrhosis stage. This was due to the absence of any clinical symptoms of the disease for a long period of time, and the lack of attention of practicing doctors in investigating the reasons for the long-term increase in transaminase activity. The trigger factor for the clinical manifestations of cirrhosis, which developed due to the long-term course of AIH, was emotional stress resulting from leaving the combat zone. The application of the International Autoimmune Hepatitis Group criteria in clinical practice was demonstrated, specifically the combination of elevated antinuclear antibodies and total IgG, characteristic histological changes in the liver, and exclusion of hepatotropic viral infections, which allowed for a reliable diagnosis of AIH. Medical treatment resulted in certain positive changes in clinical and laboratory indicators. However, according to the transplant doctor's opinion, at this stage of the AIH course, the patient required a liver transplant and therefore was added to the waiting list. Conclusions. This clinical case highlights the late diagnosis of AIH at the cirrhosis stage in a 40-year-old female patient due to the absence of clinical manifestations over several years and the lack of vigilance among doctors, possibly primary care physicians or specialists, to investigate the persistent increase in transaminase activity. The application of the International Autoimmune Hepatitis Group criteria helped confirm the diagnosis of AIH.